Narratives of Change: How Farmers Perceive the Impact of Digital Tools on Traditional Practices - Zidnal Falah; Elvira Fitriyanti; Nur Alifah; Ega Nur Fadillah (Digital Agriculture and Innovation Journal, 2025)
The adoption of digital tools in agriculture has brought significant changes, especially among traditional farmers who often rely on established practices. While digital innovations such as mobile applications, precision farming, and data analytics promise enhanced productivity and sustainability, their acceptance varies widely among farmers. This study aims to explore traditional farmers' perceptions of digital tools, focusing on factors influencing adoption, challenges in integration, and the potential benefits. A qualitative research approach was employed, using in-depth interviews and focus group discussions with a purposively selected sample of traditional farmers. Data were analyzed thematically to capture insights into attitudes, barriers, and the socio-cultural impact of digital tools on traditional practices. Findings reveal that farmers’ perceptions range from skepticism to conditional acceptance, often influenced by age, digital literacy, and cultural attachment. Key challenges include language barriers, technical complexity, and costs, with younger farmers demonstrating greater openness to adopting digital solutions. Additionally, results suggest that consistent training and support are critical for enhancing adoption rates, enabling farmers to balance traditional practices with modern tools. These insights provide practical implications for policymakers and technology developers, underscoring the need for localized training and adaptable digital solutions. This research emphasizes the importance of understanding and addressing traditional farmers' perspectives in promoting sustainable agricultural transformation.